2000
DOI: 10.1002/(sici)1097-0126(200005)49:5<437::aid-pi239>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale reinforcement of polyhedral oligomeric silsesquioxane (POSS) in polyurethane elastomer

Abstract: A unique class of polyurethane (PU) elastomer containing inorganic molecules (polyhedral oligomeric silsesquioxane, POSS) as molecular reinforcement in the hard segment was investigated by means of wide-angle X-ray diffraction (WAXD) and small-angle X-ray scattering (SAXS) techniques. WAXD results indicate that POSS molecules form nanoscale crystals showing distinct re¯ection peaks. The formation of POSS crystals is probably prompted by the microphase separation between solid-like hard segments and rubbery sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(110 citation statements)
references
References 16 publications
(19 reference statements)
7
102
0
1
Order By: Relevance
“…[4][5][6] Among them, POSS-modified elastomeric polyurethanes were also considered. [7][8][9][10] In this communication we report on the preparation and surface behavior of a new class of POSS-modified ionomeric polyurethanes with the aim to investigate the effect of nanostructure formation on the surface wettability of films applied from aqueous environment.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Among them, POSS-modified elastomeric polyurethanes were also considered. [7][8][9][10] In this communication we report on the preparation and surface behavior of a new class of POSS-modified ionomeric polyurethanes with the aim to investigate the effect of nanostructure formation on the surface wettability of films applied from aqueous environment.…”
Section: Introductionmentioning
confidence: 99%
“…The POSS molecules have been successfully incorporated into many polymers, such as styryls, acrylics, liquid-crystalline polyesters, siloxanes, and polyamides. [22][23][24][25][26][27][28][29][30][31] Either by chemical or physical means, the POSS molecules can be dispersed in the polymer matrix by the adjustment of the chemical groups attached to the silicon atoms. The addition of POSS molecules can enhance many properties, such as heat resistance, oxygen permeation, and hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al 51,52 obtained two phenolic hydroxyl POSS by hydrosilylation, and then polymerization of the POSS with 4,4'-methylenebis (phenylisocyanate) and polytetramethylene glycol resulted in high-density polyurethane, as shown in Figure 7. XRD studies found that the POSS in the system formed micro-crystals.…”
Section: Hydroxy-possmentioning
confidence: 99%